COVID-19: A Psychosocial Perspective - Raza, Syed Hassan; Haq, Wajiha; Sajjad, Muhammad (Frontiers in Psychology, 2020)
The World Health Organization declares COVID-19 as a pandemic and The World Economic Forum argues that the COVID-19-induced global lockdown is the biggest psychological experiment. This study is an attempt to empirically evaluate the possible adverse psychosocial effects caused by COVID-19-related lockdown, if any. To do so, a cross-sectional study is conducted based on a comprehensive online survey using snowball sampling to analyze the level of social and psychological impacts (i.e., stress, believe in stakeholders, fear of losing job, and life satisfaction) during the early stage of the outbreak in Pakistan. The questionnaire is filled out by the residents in Pakistan including working professionals and students (sample size is 428). We find that the development of stress due to COVID-19-induced lockdown particularly because of mood-swings. Additionally, a higher prevalence of stress in the children of highly educated mothers is evident (95% confidence). To assess the believe in stakeholders, we focus gender, demographics, and education. It is observed that parental education and age significantly affect the believe in several stakeholders (i.e., government, media, religious clerics, and family). The lockdown-induced fear of losing job is lower in females and males whose fathers are graduate. Lastly, we observe food-storage and “no fear of losing job” significantly increases the odds of life satisfaction. These findings have important implications in the context of social insurance, parental education, and policy related to COVID-19 at various levels. This study further facilitates to understand the factors which might influence the mental health and life satisfaction of people during such pandemics. Keywords: COVID-19; Public Health; Psychology; Stress